Interrater Reliability of the Modified Tardieu Scale in the Assessment of Muscle Spasticity in Stroke Patients - Nouroddin Nakhostin-Ansari; Soufia Naghdi; Gholam Reza O'liaei; Mahdi Abdolvahhab; Mahmoud Jalili; Shohreh Jalaei; Hossein Soltani-Nezhad (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Spasticity is one component of the upper motor neurone syndrome, which is characterised by a velocity dependent increase in the tonic stretch reflexes. This study aimed at investigating the interrater reliability of the Modified Tardieu Scale in the assessment of muscle spasticity in stroke patients. Materials & Methods: In this analytical and validity testing study 30 patients with spastic hemiplegia were selected by simple sampling from clients of central nervous system disorders clinic of Tehran University of medical sciences. The two muscle groups in affected upper limb were tested using a standardized procedure. These were elbow flexors and extensors. Assessment was done by the two occupational therapists during the same session. The order of assessment and the sequence of muscle testing by the two raters were random. The interrater reliability was calculated for the different subsales of Modified Tardieu. The reliability was tested with the intraclass correlation coefficient (ICC). For the Modified Tardieu Scale scores, the Cohen's Kappa test was used to analyze the level of agreement between the raters.  Results: The values of ICC for both muscle groups were high. The ICC for R2-R1 as main outcome measure for determination of spasticity severity was 0.99 and 0.95 in the flexors and extensors, respectively. The Kappa values in muscles reaction quality were 0.88 in flexors and 0.89 in Extensors. Conclusion: The Modified Tardieu Scale provides high interrater reliability in the assessment of muscle spasticity after stroke.